Determination of the melting temperature, heat of fusion, and purity analysis of different samples of zidovudine (AZT) using DSC - Adriano Antunes Souza Araújo; Marília dos Santos Bezerra; Sílvia Storpirtis; Jivaldo do Rosário Matos (Universidade de São Paulo, 2010)
The determination of chemical purity, melting range, and variation of enthalpy in the process of characterizing medicines is one of the principal requirements evaluated in quality control of the pharmaceutical industry. In this study, the method of purity determination using DSC was outlined, as well as the application of this technique for the evaluation of commercial samples of zidovudine (AZT) (raw material) supplied by different laboratories. To this end, samples from six different laboratories (A, B, C, D, E, and F) and the standard reference (R) from the United States Pharmacopeia (USP) were analyzed. The DSC curves were obtained in the temperature range of 25 to 200 ºC under the dynamic atmosphere of N2 (50 mL min-1), heating rate of β=2 ºC min-1, using an Al capsule containing approximately 2 mg of sample material. The results demonstrated that the standard reference presented a proportion of 99.83% whereas the AZT samples presented a variation ranging from 97.59 to 99.54%. In addition, the standard reference was found to present a temperature of onset of melting point of 122.80 °C. Regarding the samples of active agents provided by the different laboratories, a variation ranging from 118.70 to 122.87 °C was measured. In terms of ΔHm, the samples presented an average value of 31.12 kJ mol-1. A determinação da pureza química, a faixa de fusão e a variação de entalpia envolvida no processo de caracterização de fármacos é um dos principais requisitos avaliados no controle de qualidade em indústrias farmacêuticas. Neste trabalho é feita uma breve abordagem sobre o método de determinação de pureza utilizando DSC, assim como a aplicação desta técnica para avaliação de amostras comerciais de zidovudina (AZT) (matéria-prima) fornecida por diferentes laboratórios. Para tal, foram analisadas amostras de seis diferentes laboratórios (A,B,C,D,E e F) e a substância química de referência (R) da United States Pharmacopeia (USP). As curvas DSC foram obtidas na faixa de temperatura entre 25 a 200 ºC, sob atmosfera dinâmica de N2 (50 mL min-1), β=2 ºC min-1, utilizando cápsula de Al contendo aproximadamente 2 mg de amostra. De acordo com os resultados, pode-se observar que a substância química de referência apresentou teor igual a 99,83% e que as amostras de AZT apresentaram uma faixa de variação entre 97,59 e 99,54%. Pode-se verificar, ainda, que a substância química de referência apresentou uma temperatura onset de fusão igual a 122,80 °C. Para as amostras dos princípios ativos fornecidos pelos diferentes laboratórios, pode-se verificar uma faixa de variação entre 118,70 e 122,87 °C. No que se refere ao ΔHm, as amostras apresentaram valor médio de 31,12 kJ.mol-1.